Chemical constituents from Valeriana officinalis L. var. Iatifolia Miq. and their chemotaxonomic significance. (June 2020) - Wang, Shuliang; Zeng, Yanrong; Li, Yanan; He, Li; Hu, Zhanxing; Huang, Liejun; Gu, Wei; Yuan, Chunmao; Hao, Xiaojiang
Abstract: Twenty-one compounds, including four monoterpenoids (1 –4 ) (two new natural products, 1 and 2 ), four sesquiterpenes (5 –8 ), two iridoids (9 and 10 ), four steroids (11 –14 ), five phenolic compounds (15 –19 ), and two alkaloids (20 and 21 ), were isolated from the roots of Valeriana officinalis L. var. Iatifolia Miq. Their chemical structures were established by spectroscopic methods and further confirmed by comparison with published data in the literature. Among them, eight compounds (1, 2, 6 –8, 13, 18, and 21 ) are being reported from the family Valerianaceae for the first time, and compounds 9 –12 were obtained from V. officinalis for the first time. The chemotaxonomic significance of the isolated compounds is discussed. Graphical abstract: Image 1 Highlights: Twenty-one compounds were isolated from the roots of Valeriana officinalis L. var. Iatifolia Miq. Eight compounds (1, 2, 6 –8, 13, 18, and 21 ) are being reported from the family Valerianaceae for the first time. The chemotaxonomic significance of the isolated compounds is discussed.